The Influence of Consumer Value Perception and E-Ticket Service Quality on Traveloka Customer Satisfaction in Bandar Lampung - Ahmad Gusmawan; Satria Bangsawan; Mudji Rachmat Ramelan (International Journal of Regional Innovation, 2022)
The trend of online shopping in Indonesia continues to increase, this is evidenced by data showing that the growth of online consumers in Indonesia is increasing by 30 percent every year.In the research conducted, identifying the quality of electronic services (e-service quality) and perceived consumer value are factors that have a direct influence on consumer satisfaction and have an indirect effect on loyalty after being moderated by the variable customer satisfaction. This research focuses on airplane e-ticket services for online travel agent companies, or (online Travel Agents/OTA), namely Treveloka. The problem of this research is whether service quality and perceived value of electronic consumers have a significant positive effect on consumer satisfaction. The purpose of this researchto knowthe magnitude of the influence of electronic service quality and consumer value perceptions on consumer satisfaction. The population and sample in this study are Traveloka consumers who make repeat purchases on the Traveloka website and sites in Bandar Lampung. Data analysis using multiple linear regression. The results of this study indicate thatelectronic service quality variable has a significant positive effect of 0.379 on satisfaction. Meanwhile, the consumer value perception variable has a significant positive effect of 0.324 on satisfaction. The implications of the calculation results of consumer satisfaction and perceived consumer value are considered very good with a high level of satisfaction. However, Traveloka should provide free consultation through its website regarding complaints or procedures for arranging vacation schedules and visits to a country. Interactive interactions can increase consumer knowledge and ability to get maximum results for the services provided by the Traveloka website.